2016
DOI: 10.1038/srep24136
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between LDH serum levels and clinical outcome in advanced biliary tract cancer patients treated with first line chemotherapy

Abstract: LDH may represent an indirect marker of neo-angiogenesis and worse prognosis in many tumour types. We assessed the correlation between LDH and clinical outcome for biliary tract cancer (BTC) patients treated with first-line chemotherapy. Overall, 114 advanced BTC patients treated with first-line gemcitabine and cisplatin were included. Patients were divided into two groups (low vs. high LDH), according to pre-treatment LDH values. Patients were also classified according to pre- and post-treatment variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
21
1
1
Order By: Relevance
“…MOS in another study was quoted to be 8.7 months among LS‐SCLC patients with high s‐LDH compared to the 12 months MOS reported among patients with normal s‐LDH . Similarly, among patients with ES‐SCLC or other advanced cancers like biliary tract cancers, high s‐LDH remained a clinically significant negative prognosticator; progression‐free survival and MOS were both observed to be reduced among high s‐LDH patients at 2.6 versus 5.0 months and 5.6 versus 7.7 months, respectively . The survival data from these studies closely resembled the survival data observed in our study.…”
Section: Discussionmentioning
confidence: 54%
“…MOS in another study was quoted to be 8.7 months among LS‐SCLC patients with high s‐LDH compared to the 12 months MOS reported among patients with normal s‐LDH . Similarly, among patients with ES‐SCLC or other advanced cancers like biliary tract cancers, high s‐LDH remained a clinically significant negative prognosticator; progression‐free survival and MOS were both observed to be reduced among high s‐LDH patients at 2.6 versus 5.0 months and 5.6 versus 7.7 months, respectively . The survival data from these studies closely resembled the survival data observed in our study.…”
Section: Discussionmentioning
confidence: 54%
“…It has been in fact demonstrated that high LDH serum levels were associated with tumor overexpression of VEGFA and VEGF receptors in many tumor types. It has been postulated that LDH levels may represent an indirect marker of activated tumor angiogenesis and a worse prognosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Serum LDH is also a possible marker for metastasis, prediction of therapeutic efficacy and prognosis. [148][149][150][151] Studies on melanoma have demonstrated that ctDNA has a higher sensitivity than LDH to detect disease progression and treatment response, making it a more promising blood-based biomarker than LDH. [152,153] Mitochondria provide energy for cell functioning and contain their own genetic material, mitochondrial DNA (mtDNA), which encodes 13 proteins of the mitochondrial proteome.…”
Section: Ctdna and Tumor Metabolismmentioning
confidence: 99%